Cognitive impairments of alcoholic cirrhotic patients: correlation with endogenous benzodiazepine receptor ligands and increased affinity of platelet receptors. Issue 6 (June 1996) - Kapczinski, F; Curran, H V; Przemioslo, R; Williams, R; Fluck, E; Fernandes, C; File, S E
Abstract : OBJECTIVES–To determine whether differences in cognitive function between alcoholic and non-alcoholic cirrhotic patients relate to differences in endogenous ligands for the benzodiazepine receptor and/or benzodiazepine binding. METHODS–Seventeen grade-I hepatic encephalopathic patients (nine alcoholic, eight non-alcoholic) were compared with 10 matched controls on plasma concentrations of endogenous ligands for the neuronal benzodiazepine receptor, benzodiazepine binding in platelets, and performance on tests of cognitive function. RESULTS–Both groups of patients were impaired on verbal recall and on reaction time tasks compared with controls; alcoholic patients were also impaired on Reitan's trails test and digit cancellation. Four of the 17 patients had detectable concentrations of endogenous benzodiazepine ligands and they were more impaired than other patients on trails and cancellation tests. The groups did not differ in the density of benzodiazepine platelet receptors, but receptor affinity was higher in alcoholic patients than in controls; furthermore, receptor affinity correlated with the time to complete the cancellation task and with reaction time. CONCLUSION–Alcoholic cirrhotic patients may have enhanced concentrations of ligands for neuronal and peripheral benzodiazepine receptors and these may contribute to cognitive impairments in these patients.